Ensinando condutividade e resistividade através de jogo eletrônico: corrida eletrônica - Oliveira, Leandro Carvalho de (Universidade Federal de São Carlos, 2022)
The concepts of conduction and electrical resistance are important themes, but not much explored in the Physics teaching literature, especially in basic education. This encouraged the desire to address the topic in order to looking for mechanisms to make physics classes more attractive. In particular, through the use of technology with tools that students are used to dealing with, such as games. The educational product developed involves an adequate didactic sequence in a videogame that addresses electrical conductivity and resistivity in a playful way. The didactic sequence was designed to introduce the game in a natural and recreational way. As a theoretical framework for the assessment of learning, we adopted the theory of meaningful learning by David Ausubel. For the development of the game, the Construct 2 platform was chosen and used, which allows the construction of a 2D game in a simple and self-intuitive way. The educational product was applied to students of the 3rd grade of high school at a school located in the city of Tietê, in the interior of São Paulo. The application of the educational product was divided into 5 stages, taking into account the following order: survey of previous knowledge, lectures and dialogues, application of the game, evaluation and verification of significant learning. The results obtained in the application of the product are promising and show important points of significant learning of the students involved.
Teaching conductivity and resistivity through a videogame: corrida eletrônica
Keywords: Game; Electricity; Resistivity; Conductivity; Information and Communication Technologies; Jogo; Física; Eletricidade; Resistividade; Condutividade; Tecnologias da Informação e Comunicação; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA GERAL